Tooth fragment lodged in the lower lip after traumatic dental: a case report - Dr Chakiri Hanane; Dr Fawzi Rachid (Pediatric Review: International Journal of Pediatric Research, 2015)
In permanent teeth, the crown fracture is often associated with lesions in the surrounding oral tissues particularly at cold which can lead to serious complications.In the presence of a lip edematous, open and / or shredded associated with a coronal fracture, thorough clinical and radiographic examination of soft tissue must be systematic.In fact, lesions of the lip can cover up any foreign bodies or fragments of dental crowns embedded in the wounds.The orbicularis muscle pain on palpation mask their presence making the impalpable and only an X-ray may highlight them.Through this article based on a clinical case, we will describe the process for the diagnosis of including dental fragment at labialis after a dentoalveolar trauma, and the terms of the management.